2007
DOI: 10.1080/09637480601041086
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements and dietary habits of schoolchildren in Qatar

Abstract: schoolchildren in Qatar may be considered as having less overweight and obesity occurrence than most children in the Gulf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…This is especially true when we compare our findings with those previously reported by Musaiger and Gregory (11) where none of the school children mentioned that they consumed fast foods. Studies in Arab Gulf countries (57) have shown that fast foods are now becoming an integral part of the lifestyle of school children. The fact that girls consume fast foods more at home than the boys could be due to cultural restrictions on travel and ease of home delivery from fast food restaurants that have become very popular in Bahrain in the past few years, especially among the younger generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true when we compare our findings with those previously reported by Musaiger and Gregory (11) where none of the school children mentioned that they consumed fast foods. Studies in Arab Gulf countries (57) have shown that fast foods are now becoming an integral part of the lifestyle of school children. The fact that girls consume fast foods more at home than the boys could be due to cultural restrictions on travel and ease of home delivery from fast food restaurants that have become very popular in Bahrain in the past few years, especially among the younger generation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the Arabian Gulf countries (including Bahrain), poor dietary habits such as skipping breakfast, a low intake of milk, fruits, and vegetables; and a high intake of carbonated beverages, sweets, and fast food were reported by several studies on school children (57). In addition, the significant epidemiological transformations that have occurred over the past two or three decades have resulted in the modification of the lifestyle to a more sedentary way of living, with considerable reduction in the extent of physical activity, an increase in the intake of fast foods, and the elevation of stress-related work and other activities (8).…”
mentioning
confidence: 99%
“…In Abha City (South western of Saudi Arabia) in 2008, the prevalence of overweight and obesity estimated to be 16% (Amin, Al-Sultan, & Ali, 2008). While in Qatar (2007), the overall prevalence of overweight and obesity was 9.5% (6% were overweight and 3.5% were obese) (Qotba & Al-Isa, 2007). The prevalence of overweight and obesity in this study was markedly lower than that reported for American children, where the overall prevalence of overweight and obesity was 48.0% (16.5% were bese, and 31.5% were overweight) (Ogden, Carroll, Curtin, Lamb, & Flegal, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Skipping breakfast, decreased consumption of fruits and dairy and increased consumption of fast food and sweetened or energy drinks has been reported in many studies, both in the West, Eastern Mediterranean region and the Gulf [4,9,12,18,31,38]. This type of diet is strongly associated with the incidence of obesity and other chronic diseases such as type 2 diabetes and hypertension [40].…”
Section: Discussionmentioning
confidence: 99%